Research needs of sustainable development - Sue Scott (The Economic and Social Research Institute (ESRI), 2004)
The understanding of natural laws underlies the research programme so that we can 'obey nature' and thereby develop in a sustainable way - but let us not forget that human behaviour is part of nature's ways too. Human nature must also be understood. Socio-economic research, which looks into how people are motivated and interact with resources, is essential to help guide behaviour because it is the human activities that are environmentally unsustainable.
Keywords: 330